Gamification in employee selection: The development of a gamified assessment - Georgiou, Konstantina; Gouras, Athanasios; Nikolaou, Ioannis (International journal of selection and assessment, 2019)
Gamification has attracted increased attention among organizations and human resource professionals recently, as a novel and promising concept for attracting and selecting prospective employees. In the current study, we explore the construct validity of a new gamified assessment method in employee selection that we developed following the situational judgement test (SJT) methodology. Our findings support the applicability of game elements into a traditional form of assessment built to assess candidates' soft skills. Specifically, our study contributes to research on gamification and employee selection exploring the construct validity of a gamified assessment method indicating that the psychometric properties of SJTs and their transformation into a gamified assessment are a suitable avenue for future research and practice in this field.